Effect of different tropical roughages on nutrient digestibility and rumen fermentation parameters of West African Dwarf sheep during dry season - AKINBODE, R M; ISAH, O A; ONI, A O; ADEWUMI, O O; OMONIYI, L A (The Indian Journal of Animal Sciences, 2014)
This experiment was designed to determine the effect of selected tropical roughages on digestibility and rumen parameters of West African dwarf sheep. West African dwarf female sheep (24) weighing 12.2 ±0.26 kg, were allocated to 4 treatments in a completely randomized design. The experimental animals were fed on Panicum maximum hay (PAHA, T1), 5% urea-treated corn cob (UTCC, T2), 5% urea-treated sugarcane top (UTST, T3) and cassava hay (CAHA, T4). Results showed highest dry matter (DM) intake (575.74 g/day) in sheep fed on UTST while DM intake was lowest in those fed on UTCC (377.04 g/day). Dry matter, neutral detergent fibre and acid detergent fibre digestibilities were highest in sheep fed on UTST while crude protein digestibility was highest in animals fed on CAHA. Rumen NH3-N and blood urea nitrogen (BUN) concentrations were high in animals fed on CAHA. Total VFA (116.00 mM), acetate (70.85 mol/100ml) and propionate (23.40 mol/100ml) concentrations were highest in sheep fed on PAHA. Protozoa, fungal and total viable bacteria counts were different across the treatments. This study revealed that UTST, PAHA and CAHA could be utilized for productive purposes while UTCC could serve as a maintenance ration for West African dwarf sheep during the long period of dry season when grasses are not available.